USE OF ANALYTICAL TRANSFORMATIONS IN TASKS OF IMAGES COMPRESSION - Юдін, О. К.; Курінь, К. О.; Варченко, О. І. (Science-based technologies, 2011)
The analysis of existent algorithms of transformation of images is provided. The mathematical models of trans-formations are considered, among them: discrete cosine transformation, discrete wavelet transformation, trans-formation of Haar, transformation of Walsh-Hadamard. Marked mathematical models are realized programmatic with the tools of Mathcad. The calculation of characteristics which determines efficiency of transformations for a test image is conducted. Cross-correlation of values of brightness of nearby pixels and redistribution of dispersions between the values of brightness of even and odd pixels of image are chosen as such characteristics.